Key Factors in Labor Relations and Conflict Management in Hotel Organizations: Application to the identification of employee profiles and actionable variables - Vicente Pascual, José Antonio; Paradinas Márquez, María del Carmen (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The objective of the study is the conflicts produced in the hotels and their impact on the structure and image projected in front of the client, especially the deterio- ration of the work of the teams when there is no confrontation of the conflict, or it is managed incorrectly. The study aims to identify those key elements in conflict management and labour relations, identifying on the one hand those elements that are correctly managed, as well as the elements where there is room for improve- ment. Additionally, it tries to determine which are those variables that allow us to identify different behaviours in this area.